Ownership Networks and Bid Rigging - Asai, Kentaro; Charoenwong, Ben (The Review of Corporate Finance Studies, 2026)
Abstract Using a data set of public procurement auctions and registered shareholders of all bidding firms in Singapore, we study the effects of ownership networks on prices and efficiency in product markets. We find participating bidders with common owners or common owners’ owners are more likely to submit identical bids, and the identical bids are associated with higher contract prices. Our structural estimates suggest removing ownership network effects improves a procurer’s cost efficiency. Our findings are robust to falsification tests, bid rounding concerns, placebo tests using other common stakeholder relationships, and weighting based on a machine-learning prediction of the auction format.